2009
DOI: 10.1136/gut.2008.157016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteasome level is a reliable early marker of malignant transformation of liver cirrhosis

Abstract: The plasma proteasome level is a reliable marker of malignant transformation in patients with cirrhosis, even when there is a low tumour mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
4
25
0
Order By: Relevance
“…The results for healthy subjects are, in general, consistent with those obtained by other investigators, who, using ELISA-based assay have demonstrated that the average concentrations of plasma 20S proteasome in the controls are between 2100 and 2600 ng·mL-1 [1719, 21]. However, it should be mentioned that other groups of investigators have demonstrated that 20S proteasome antigen concentration in plasma or serum from normal subjects was less than 400 ng·mL-1 [16, 20, 40].…”
Section: Resultssupporting
confidence: 90%
“…The results for healthy subjects are, in general, consistent with those obtained by other investigators, who, using ELISA-based assay have demonstrated that the average concentrations of plasma 20S proteasome in the controls are between 2100 and 2600 ng·mL-1 [1719, 21]. However, it should be mentioned that other groups of investigators have demonstrated that 20S proteasome antigen concentration in plasma or serum from normal subjects was less than 400 ng·mL-1 [16, 20, 40].…”
Section: Resultssupporting
confidence: 90%
“…So far, circulating proteasome has been detected in patients with solid tumors using the ELISA test employing antibodies directed against the constitutive α subunits of the 20S proteasome [25][26][27][28][29][30]. However, ELISA-based assay Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular proteasome has been proposed as a suitable biomarker in some cancers and autoimmune diseases, potentially allowing for better diagnosis, patient stratification, and prediction of the response to therapy18192021, even though its function is not yet understood. Here, we elucidate one of its potential functions in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…microparticle/ectosomes shedding from the surface of T lymphocytes16, or exosomes derived from endocytic compartments of mesenchymal stem cells17. In patients with solid tumors and hematological malignancies, extracellular proteasome levels increase and correlate with occurrence, severity, as well as clinical outcome of the diseases181920. In some autoimmune diseases, such as rheumatoid arthritis, MS and systemic lupus erythematosus, extracellular proteasome levels are increased and are markers of cell damage and immunological activity2122.…”
mentioning
confidence: 99%